2018
DOI: 10.5194/hess-22-2449-2018
|View full text |Cite
|
Sign up to set email alerts
|

Root growth, water uptake, and sap flow of winter wheat in response to different soil water conditions

Abstract: Abstract. How much water can be taken up by roots and how this depends on the root and water distributions in the root zone are important questions that need to be answered to describe water fluxes in the soil-plant-atmosphere system. Physically based root water uptake (RWU) models that relate RWU to transpiration, root density, and water potential distributions have been developed but used or tested far less. This study aims at evaluating the simulated RWU of winter wheat using the empirical Feddes-Jarvis (FJ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
60
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 73 publications
5
60
3
Order By: Relevance
“…In addition to updating water stress, PHS implements updated RWU, consistent with hydraulic theory (Cai et al, ; Warren et al, ). The parameterization of RWU affects the vertical distribution of soil water (Figures and S9), as SMS tends to achieve drier upper soil layers, whereas PHS spreads the drying effects of transpiration over a larger vertical extent.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to updating water stress, PHS implements updated RWU, consistent with hydraulic theory (Cai et al, ; Warren et al, ). The parameterization of RWU affects the vertical distribution of soil water (Figures and S9), as SMS tends to achieve drier upper soil layers, whereas PHS spreads the drying effects of transpiration over a larger vertical extent.…”
Section: Resultsmentioning
confidence: 99%
“…Cai et al. () concluded that new root growth was a mechanism leading to RWU activity increase after rewetting.…”
Section: Discussionmentioning
confidence: 99%
“…Green and Clothier (1995) found that root activities after rewetting were greater than during the drying period. Cai et al (2018) concluded that new root growth was a mechanism leading to RWU activity increase after rewetting.…”
Section: Resumption Of Rwu After Rewettingmentioning
confidence: 99%
See 1 more Smart Citation
“…Because root system conductance tends to scale with root length, the root conductance per unit root length was assumed invariant in order to accommodate for root growth. Such a constraint also matters when accounting for the spatial heterogeneity of root development under different soil/microclimate environments in macroscale simulations [101] . …”
mentioning
confidence: 99%